RNA interference mediated inhibition of dengue virus multiplication and entry in HepG2 cells - Alhoot, M.A.; Wang, S.M.; Sekaran, S.D. (Public Library of Science, 2012)
BACKGROUND: Dengue virus-host cell interaction initiates when the virus binds to the attachment receptors followed by endocytic internalization of the virus particle. Successful entry into the cell is necessary for infection initiation. Currently, there is no protective vaccine or antiviral treatment for dengue infection. Targeting the viral entry pathway has become an attractive therapeutic strategy to block infection. This study aimed to investigate the effect of silencing the GRP78 and clathrin-mediated endocytosis on dengue virus entry and multiplication into HepG2 cells. METHODOLOGY/PRINCIPAL FINDINGS: HepG2 cells were transfected using specific siRNAs to silence the cellular surface receptor (GRP78) and clathrin-mediated endocytosis pathway. Gene expression analysis showed a marked down-regulation of the targeted genes (87.2%, 90.3%, and 87.8% for GRP78, CLTC, and DNM2 respectively) in transfected HepG2 cells when measured by RT-qPCR. Intracellular and extracellular viral RNA loads were quantified by RT-qPCR to investigate the effect of silencing the attachment receptor and clathrin-mediated endocytosis on dengue virus entry. Silenced cells showed a significant reduction of intracellular (92.4%) and extracellular viral RNA load (71.4%) compared to non-silenced cells. Flow cytometry analysis showed a marked reduction of infected cells (89.7%) in silenced HepG2 cells compared to non-silenced cells. Furthermore, the ability to generate infectious virions using the plaque assay was reduced 1.07 log in silenced HepG2 cells. CONCLUSIONS/SIGNIFICANCE: Silencing the attachment receptor and clathrin-mediated endocytosis using siRNA could inhibit dengue virus entry and multiplication into HepG2 cells. This leads to reduction of infected cells as well as the viral load, which might function as a unique and promising therapeutic agent for attenuating dengue infection and prevent the development of dengue fever to the severe life-threatening DHF or DSS. Furthermore, a decrease of viremia in humans can result in the reduction of infected vectors and thus, halt of the transmission cycle.